2017
DOI: 10.1093/mnras/stx1706
|View full text |Cite
|
Sign up to set email alerts
|

Simulating neutron star mergers as r-process sources in ultrafaint dwarf galaxies

Abstract: To explain the high observed abundances of r-process elements in local ultrafaint dwarf (UFD) galaxies, we perform cosmological zoom simulations that include r-process production from neutron star mergers (NSMs). We model star-formation stochastically and simulate two different halos with total masses ≈ 10 8 M at z = 6. We find that the final distribution of [Eu/H] vs. [Fe/H] is relatively insensitive to the energy by which the r-process material is ejected into the interstellar medium, but strongly sensitive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 71 publications
1
59
0
Order By: Relevance
“…Depending on the coalescence timescales of NS-NS mergers and on the velocity of those kicks, it is possible for NS-NS binaries to merge outside galaxies (e.g., Bloom et al 1999;Fryer et al 1999;Belczynski et al 2006;Zemp et al 2009;Kelley et al 2010;Behroozi et al 2014;Safarzadeh & Côté 2017). The simulations of Safarzadeh & Scannapieco (2017) showed that the spatial location of NS-NS mergers can play an important role on the amount of r-process material recycled into stars.…”
Section: Impact Of Natal Kicksmentioning
confidence: 99%
“…Depending on the coalescence timescales of NS-NS mergers and on the velocity of those kicks, it is possible for NS-NS binaries to merge outside galaxies (e.g., Bloom et al 1999;Fryer et al 1999;Belczynski et al 2006;Zemp et al 2009;Kelley et al 2010;Behroozi et al 2014;Safarzadeh & Côté 2017). The simulations of Safarzadeh & Scannapieco (2017) showed that the spatial location of NS-NS mergers can play an important role on the amount of r-process material recycled into stars.…”
Section: Impact Of Natal Kicksmentioning
confidence: 99%
“…In particular, Côté et al (2018) compares high-resolution hydrodynamics simulations directly with one-zone models, finding the importance of non-uniform mixing in driving abundance spreads in these galaxies, and characterize multiple hydrodynamics effects that are challenging to parameterize in current one-zone models. Additional works have conducted more direct investigations into what drives the enrichment process for individual sources using both hydrodynamics simulations (Pan et al 2013;Ritter et al 2015;Safarzadeh & Scannapieco 2017;Hirai et al 2015;Hirai & Saitoh 2017;Emerick et al 2018;Haynes & Kobayashi 2019) and semianalytic models (e.g. Krumholz & Ting 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly,Safarzadeh & Scannapieco (2017) finds that the resulting abundance patterns in a UFD candidate at high redshift are generally insensitive to the energy of the injection event. However, they focus on enrichment events from a smaller range of injection energies: 10 50 -10 51 erg.…”
mentioning
confidence: 99%
“…These would come from performing high resolution zoom cosmological simulations on UFD host halos while modeling the candidate DNSs as r -process sources with their characteristic natal kicks and merging times. While we have shown in Safarzadeh & Scannapieco (2017) that a single NSM event can explain Reticulum II like systems, these sets of simulations are vital to perform, since otherwise the impact of natal kicks remains unclear. The ejected r -process material might not get effectively recycled into the new generation of the stars (Macias & Ramirez-Ruiz 2018).…”
Section: Tucana III Progenitor Stellar Massmentioning
confidence: 99%
“…Separately, through cosmological zoom simulations of UFDs, Safarzadeh & Scannapieco (2017) demonstrated that a single NSM event can account for the observed r -process enrichment in Reticulum II, with modest assumptions regarding the europium yield in the dynamical ejecta of the NSM. However, the authors had to make the NSM event take place in less than about 10 Myr after the onset of star formation in the UFDs so that the subsequent generation of stars can inherit the r -process ejected into the interstellar medium (ISM) before the total stellar mass of the system reaches M ≈ 10 4 M .…”
Section: Introductionmentioning
confidence: 99%